The availability of cues for word segmentation and vocabulary acquisition in Catalan child-directed speech - FEIJÓO,SARA (Universidad de Concepción. Facultad de Humanidades y Arte, 2013)
Several previous studies have already pointed out the usefulness of child-directed speech for several tasks during the language acquisition process. In particular, recent research suggests that the kind of structural and lexical simplifications found in the type of language especially addressed to language learning infants (i.e. utterance length and lexical redundancy) are particularly useful for preverbal infants' initial word segmentation of the speech stream. While most research conducted to date is based on English data, little is known about the facilitation effects that child-directed speech might have in other languages. The present study aims at providing cross-linguistic evidence for the usefulness of child-directed speech by analyzing speech samples addressed to Catalan-learning children.